Identify the second step in solving this equation for y -3(y-6)=21

1 answer

The second step in solving the equation -3(y-6)=21 is to simplify the expression inside the parentheses.

To do this, distribute the -3 to both terms inside the parentheses:

-3(y-6) = -3 * y + (-3) * (-6)
= -3y + 18

So, the simplified equation becomes -3y + 18 = 21.
Similar Questions
  1. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 3 answers
  2. Solving the equation 6x + 2(x − 1) = 30Given: 6x + 2(x − 1) = 30 Step 1: 6x + 2x − 2 = 30 Step 2: 8x − 2 = 30 Step 3: 8x
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions